2010
DOI: 10.4097/kjae.2010.59.3.210
|View full text |Cite
|
Sign up to set email alerts
|

Conversion phenomenon during the induction period of general anesthesia -A case report-

Abstract: Conversion disorder is characterized as psychological symptoms such as somatization and emotional distress, but there is no abnormal electrical signal in the brain. We report a patient who appeared conversion disorder during the induction period of general anesthesia. A 45-year-old woman was planned for arthroscopic knee meniscectomy. In the operating room, she appeared stable, but she said extremely nervous in this situation. Before propofol injection for induction of anesthesia, we injected 1% lidocaine 50 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…CD morbidity reaches up to 33%. [ 8 ] The diagnosis is usually challenging as the patient with CD has complex presentation. [ 9 ] The diagnostic criteria according to the DSM-5 (Diagnostic and Statistical Manual of Mental Disorders, fifth edition), for CD are: a) one or more of voluntary motor or sensory deficit, b) clinical findings that show evidence of incompatibility between the symptoms and recognized neurological or medical conditions, c) symptom or deficit that is not explained by another medical or mental disorder, d) symptom or deficit that cause clinically significant distress or impairment in social, occupational, or other vital areas of functioning and deserves medical evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…CD morbidity reaches up to 33%. [ 8 ] The diagnosis is usually challenging as the patient with CD has complex presentation. [ 9 ] The diagnostic criteria according to the DSM-5 (Diagnostic and Statistical Manual of Mental Disorders, fifth edition), for CD are: a) one or more of voluntary motor or sensory deficit, b) clinical findings that show evidence of incompatibility between the symptoms and recognized neurological or medical conditions, c) symptom or deficit that is not explained by another medical or mental disorder, d) symptom or deficit that cause clinically significant distress or impairment in social, occupational, or other vital areas of functioning and deserves medical evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these anesthetics may cause neurotoxicity to a certain extent, affecting brain development or causing cognitive impairment [ 2 ]. Kim et al [ 3 ] pointed out that patients showed obvious hysterical somatic disorders during GA induced by propofol combined with lidocaine. GA will cause increased hemodilution due to infusion of crystalloid solution, leading to changes in plasma volume [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is at least twice as common in females and occurs in children and adults [ 1 , 2 ]. Published diagnoses of CD in the perioperative setting are limited to several case reports that describe symptoms including non-epileptic seizures on induction, hemiplegia, and quadriplegia after regional and general anesthetics [ 3 , 4 , 5 , 6 ]. Here we describe a case of conversion disorder that presented as new onset incomplete quadriplegia in a healthy female after a routine anesthetic.…”
Section: Introductionmentioning
confidence: 99%